Improving the Mechanism for Bank Reorganization - Pashchenko Yuliia P. (Bìznes Inform, 2018)
The article is aimed at deepening the theoretical bases of the bank reorganization processes in Ukraine and determining practical recommendations on improving the mechanism for their implementation. The approaches to definition of the concept of «reorganization of bank» are considered and systematized; the author’s own definition of the concept of «reorganization of bank» is highlighted. The carried out economic-mathematical modeling has allowed to estimate the value of transactions of mergers and acquisitions and has caused possibility to make forecast of further situation in the market of mergers and acquisitions of banks of Ukraine. Ways of improvement of banks reorganization processes as to their financial recovery and entering the European and global markets are suggested. The issues of diagnosing the status of reorganization of banks in the context of developing practical recommendations for managerial decision-making require further research.